Uma análise da avaliação em matemática no desenvolvimento de atividades da robótica educacional - Santos, Aline Regina dos (Universidade Federal de São Carlos, 2024)
With this work we seek to understand how the assessment of mathematics skills and abilities occurs during educational robotics classes. We investigated the possibility of developing an assessment instrument using educational robotics for use in regular classes of 30 students, as the literature indicates that robotics offers educational benefits. To this end, we outline the following specific objectives: evaluate the performance of mathematics skills and abilities during activities in robotics classes and classify learning according to the Van Hiele Geometry Learning Model; Check which pedagogical trend, among those described by José Carlos Libâneo, robotics classes best identify with; Describe how the performance of mathematics skills and abilities were identified during classes in this Case Study; Track in Dissertations, the contents (objects of knowledge) Mathematicians involved in research involved in Mathematics and Educational Robotics and; identify the way in which researchers verified the learning performance of students in educational robotics classes. To achieve these objectives, theoretical references on school assessment were developed, such as Cipriano Carlos Luckesi and Jussara Hoffmann, who in their texts explain the vision of other theorists who were committed to the issue of school assessment. We present a brief history of Educational Robotics. The work methodology is Case Study and Bibliographic Research. The Case Study included the participation of 17 students aged eight and nine from a municipal school in Porto Feliz. Data are collected through participant observation, interaction of written and practical activities, interactions between students and the teacher. In Bibliographic Research, data were collected from dissertations and theses in the Google Scholar work database and the NUPEME group. Among the results, we highlight that the assessment of mathematics skills, during Educational Robotics classes, occurs in a qualitative way.
An analysis of mathematics assessment in the development of educational robotics activities
Keywords: Estudo de Caso; Avaliação; Matemática; Robótica Educacional; Case Study; Assessment; Mathematics; Educational Robotics; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::AVALIACAO DA APRENDIZAGEM